Constitutionalism in the Americas - Crawford, Colin; Bonilla Maldonado, Daniel (Studies in comparative law and legal culture, 2018)
Constitutionalism in the Americas unites the work of leading scholars of constitutional law, comparative law and Latin American and U.S. constitutional law to provide a critical and provocative look at the state of constitutional law across the Americas today. The diverse chapters employ a variety of methodologies - empirical, historical, philosophical and textual analysis - in the effort to provide a comprehensive look at a generation of constitutional change across two continents. The authors document surprising changes, including the relative decline in the importance of U.S. constitutional jurisprudence outside U.S. borders and the growing exchange of Latin American constitutional thought within Europe and beyond. Accompanying commentary elaborates on the role of constitutional law in global changes in political, social and economic power and influence. The chapters also prompt thinking about a wide range of topics important not just in the Americas, but across the world, including the challenges and implications of using legal transplants and, conversely, the utility and potential of borrowing and adapting constitutional and other legal models to different realities. This book is useful not only for advanced students of constitutional law and theory but also for students new to the area and eager to tap into the newest thinking about constitutional law and law-making in the Americas and elsewhere.